Effectiveness Of Raw White Under Consumption On Decreasing Hypertension In Elderly - Arianti (Journal of Applied Nursing and Health, 2019)
Background: Hypertension is often referred to as a "silent killer" (Stealth Killer) because often hypertension sufferers increase in years no one has a problem or complication and without realizing it the patient has been complicated on vital organs such as the brain or kidney disease. Objective To find out whether there is Effectiveness of Raw Garlic Consumption on Decreasing Hypertension in the Elderly in the Binontoan Health Center Work Area.The design used in the study was a pre-experimental post-test pretest. Population is All Seniors in the Binontoan Health Center Work Area. A large sample of 67 respondents. Using the Independent Variable Purposive sampling technique. The dependent variable is blood pressure. Data was collected using a questionnaire, then the data were analyzed using paired tests with a significance level of α ≤ 0.05.The results showed that nearly half of the respondents had severe hypertension before the intervention as many as 33 respondents (49.3%), moderate hypertension with age> 65 years as many as 20 respondents (29.9%). severe hypertension with female gender as many as 21 respondents (31.3%). moderate hypertension after intervention as many as 42 respondents (62.7%). severe hypertension with elementary education as many as 16 respondents (23.9%). severe hypertension by not working as many as 16 respondents (23.9%). have severe hypertension with no disease as many as 24 respondents (35.8%). The statistical test in this study used the Wilcoxon test with a <0.05 obtained p = 0,000 where H1 was accepted and H0 was rejected which means that there is an effect of Raw Garlic Consumption on Decreasing Hypertension in the Elderly in the Binontoan Community Health Center Working Area